The rise of film production locations and specialised film services in European semi-peripheries - Stachowiak, Krzysztof; Stryjakiewicz, Tadeusz (Hungarian Geographical Bulletin, 2018)
The research on a creative economy has been gaining momentum globally in the recent years, but the associated concepts such as the cultural economy, the creative class, creative cities and so on, have typically been urban or national in orientation. There is evidence showing that many important developments in creative industries take place now in almost all parts of the globe. One of the creative industries which may serve as a vivid example of the complex interplay between the global core and the local periphery is film industry. The paper aims to discuss rise of film production locations and specialised film services in European global semiperipheries. Globalisation of film industry involves the expansion of production away from the established and globally recognised centres, such as Hollywood or Western Europe. While some researchers refer to this development as a ‘runaway production’, this paper examines it through a broader look to core-periphery relations and points out their implications and consequences from the perspective of European countries (with a focus on post-socialist countries of East Central Europe).